Doing Understanding in Transient, Multilingual Communities in Higher Education. (18th December 2017) - Moore, Emilee
Abstract : This article analyzes interactions taking place in two transient communities involving local and international actors at a Catalan university. In scenarios in which established norms for language use are less available, people from different language backgrounds face the practical issue of establishing a common means for accomplishing understanding. This study examines how participants in the encounters establish a plurilingual medium of interaction, despite other solutions being available to them. It further proposes the notion of "doing understanding" to refer to the situated, jointly constructed and embodied performance of sharing repertoires. The results demonstrate how participants locally construct and challenge norms and possibilities of language use in transient communities in international higher education, supporting more critical consideration of how languages should be categorized by universities in their internationalization pursuits in seeking harmony with linguistic diversity.